The Model of Communication of Education in the Village Unit Cooperatives (KUDs) and in the Traditional Islamic Boarding School Cooperatives (Kopontren): A Study in West Java Province, Indonesia. (European Journal of Social Sciences, 2023)
This purpose of this research is to describe it the differences between the pattern of educational communication in the Village Unit Cooperatives (KUDs) and that in the Traditional Iskamic Boarding School Cooperatives (Kopontrens) in West Java Province, Indonesia. The research was carried out with qua litative approach on 12 KUDs and 12 Kopontrrens in West Java Province, Indonesia. The idea of the research was based on the International and Indonesian Cooperative Princ iples the which obliges the cooperative's to arrange cooperative education program for the cooperative's members and based on the facts of the cultural differences between backgroun d KUDs and Kopontrens. The result of the research indicated that educational communication in the K opontrens is stronger than that in the KUDs Because The process of educational communication process in the Kopontrens has Become a standardized educational program, so that the elements of communication process consisting of "who says w hat to Whom in roomates channel, in what effect and environtment ” has become a package of the educational communication curriculum in Kopontrens . This could explain why the members' particip ation in the Kopontrens is better than that in the KUDs. This result is a method of developing social and policy implication for developing methods for educatin in the KUDs in Indonesia.